Unprotected strike action in South Africa - Van Heerden, Andre (Department of Commercial Law, 2020)
The right to strike is an important element of collective bargaining in South Africa. While protected strike action provides significant protection to employees and employers alike, unprotected strike action does not. Given the potential adverse consequences of engaging in unprotected strike action it is important that the delineation between protected and unprotected strike action be made clear to all parties concerned, including employees, employers and trade unions. This involves a discussion of what conduct amounts to strike action in the first instance as well as a discussion of the procedural and substantive requirements which must be satisfied in order to avoid strike action being rendered unprotected. It is the purpose of this dissertation to provide such clarity. In order to do so recent amendments to labour legislation have been taken into account; The Code of Good Practice: Collective Bargaining, Industrial Action and Picketing will also be considered.